STUDI PERBANDINGAN PENGATURAN PEMBERHENTIAN PRESIDEN DAN ATAU WAKIL PRESIDEN ANTARA INDONESIA DENGAN INDIA ATAS PERBUATAN TERCELA - Robert Reiman Simanullang; Mexsasai Indra; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the constitutional system, there is an institution called impeachment. Manyparties understand that impeachment is the downfall, cessation, or dismissal ofthe President or high-ranking officials from office. In fact, the meaning ofimpeachment itself is an accusation or indictment so that impeachment focusesmore on the process and does not necessarily end with the cessation or removalof the President and other high-ranking state officials from office. Each countrythat has adopted the provisions on impeachment regulates these mattersdifferently, in accordance with the arrangements in the constitution. In Indonesia,there are grounds for impeachment of the President, one of which is misconduct,where there is still no clarity regarding the regulation of misconduct both in the1945 Constitution and other laws. Misconduct as a reason for impeachment ofthe President in Indonesia is still multi-interpreted, making it a rubber articlethat can be "played" by the House of Representatives. Therefore, it is necessaryto have a comparative country to find a clear arrangement regarding the reasonsfor misconduct as a reason for impeachment of the President, in this case, Indiais the comparative country.This research is normative legal research. It is based on library researchthat takes quotations from reading books or supporting books related to theproblem under study. This research uses secondary data sources consisting ofprimary, secondary, and tertiary legal materials. This research also usesqualitative data analysis and produces descriptive data.From the results of the research and discussion conducted, it is necessary tohave certainty regarding the regulation of criteria or standardization ofmisconduct to be used as a reason for impeachment of the President in Indonesia,so that the reason for misconduct cannot be used as a rubber article that can be"played" by the House of Representatives. There is also a need for a moreefficient dismissal mechanism so that it does not take too long.Keywords: President; Impeachment; reprehensible deeds